“Control biológico in vitro de Colletotrichum gloesporioides causante de la antracnosis frente a Clonostachys rosea, Fusarium oxysporum y Trichoderma harzianum.” - Flores Bazauri, Walter Daniel (2016)
In this research the biological control of Colletotrichum gloeosporioides, which causes anthracnose in crops of economic interest, was evaluated. The pathogen faced the following antagonistic microorganisms: Clonostachys rosea, Fusarium oxysporum and Trichoderma harzianum. Agar Sabouraud Dextrose (DSA) and Agar Papa Dextrosa (PDA) were used at different temperatures and in dual cultures. The percentage of inhibition, degree of antagonism and the rate of growth of the colonies were evaluated. It was found that the most effective antagonist was Trichoderma harzianum, which reached a degree 2 on the Bell scale (75% of the medium surface), in a culture medium Papa Dextrose Agar at 10°C 20°C and 30°C to 3, 6, 9 and 12 days of development. In addition, it was demonstrated that C. gloesporioides reached a degree 3 on the Bell scale (50% of the surface of the medium) when it faced C. rosea and F. oxysporum, both at 10°C. 20°C and 30°C in the different culture media Sabouraud Agar Dextrose and Papa Dextrose Agar, concluding that: The best biological controller of C. gloeosporioides was T. harzianum reaching a grade 2 in PDA and DSA according to the scale of Bell at 10°C, 20°C and 30°C; That the antagonistic action of C. rosea and F. oxysporum reached a grade 3 in PDA and DSA according to the Bell scale at 10° C, 20° C and 30°C against the growth of C. gloeosporioides; That the highest percentage of growth inhibition of C. gloeosporioides was also for T. harzianum with 65.12% at 30 ° C in PDA whereas in the DSA culture medium at 30° C the highest percentage of inhibition of C. gloeosporioides was for C. rosea with 27.35%, thus determining that the temperature does not influence the determination of the antagonistic control (Bell scale) but against the percentage of inhibition there is a influence of the temperature. Proving this way that Colletotrichum gloeosporioides, is a fungus whose pathogenic potential is a wide-ranging source yet to be investigated. Keywords: